Land of Extremes : A Natural History of the Arctic North Slope of Alaska - Huryn, Alexander D. (Book collections on Project MUSE., 2012)
This book is a comprehensive guide to the natural history of the North Slope, the only arctic tundra in the United States. The first section provides detailed information on climate, geology, landforms, and ecology. The second provides a guide to the identification and natural history of the common animals and plants and a primer on the human prehistory of the region from the Pleistocene through the mid-twentieth century. The appendix provides the framework for a tour of the natural history features along the Dalton Highway, a road connecting the crest of the Brooks Range with Prudhoe Bay and.